25. FACTORS EFFECT TO THE RESULT OF TREATMENT OF CORAL KIDNEY STONE PATIENTS BY MINI PERCUTANEOUS NEPHROLITHOTOMY AT SAINT PAUL HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objectives: Evaluation of stone clearance rate after treatment of coral kidney stones by small tunnel endoscopic lithotripsy at Saint Paul General Hospital and some related factors. Methods: Analytical cross-sectional description of 89 patients with recurrent coral kidney stonesnephrolithiasis treated with small-tunnel percutaneous endoscopic lithotripsy. Results: Patients aged 41-60 years old accounted for 66.3%. The number of male patients accounted for 60.7%; patients with only normal BMI accounted for 77.5%. Results of endoscopic percutaneous lithotripsy, the rate of stone clearance after 3 days is: 89.9%, after 1 month is 94.4%. The overall hospital stay was 12.9 ± 6.39 days. Overall outcome after surgery in patients: 89.9% good, 7.9% average, 2.2% bad, postoperative complications accounted for 14.6%. The study did not find a statistically significant relationship between the rate of stone clearance and BMI, between the rate of stone clearance and the stone surface area, the relationship between the rate of stone clearance and the degree of dilatation of the renal pelvis, and between the rate of stone clearance and the rate of stone clearance clean stones with puncture site (p > 0.05).Conclusion: Treatment of coral kidney stones by percutaneous endoscopic lithotripsy at Saint Paul Hospital is a safe and effective method with high stone clearance rate, stone size factors and stone surface area with high related to the rate of stone clearance after lithotripsy.
Keywords: Coral kidney stones; endoscopic lithotripsy, size.